2016
DOI: 10.1242/dmm.022012
|View full text |Cite
|
Sign up to set email alerts
|

A New Gestational Diabetes Mellitus Model, Hyperglycemia-Induced Eye Malformation via Inhibiting Pax6 in Chick Embryo

Abstract: Gestational diabetes mellitus (GDM) is one of the leading causes of fetal malformations. However, few models have been developed to study the underlying mechanisms of GDM-induced fetal eye malformation. In this study, a high concentration of glucose (0.2 mmol per egg) was injected into the air sac of chick embryos on embryo development day (EDD) 1 to develop a hyperglycemia model. Results showed that 47.3% of embryonic eye malformation happened on EDD 5. In this model, the key genes regulating eye development,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…This assumption has been supported by a study using a chick embryo model in which a high concentration of glucose injected on embryo development day (EDD) 1 resulted in 47.3% of embryonic eye malformations occurring on EDD 5 [37]. Second, enhanced oxidative stress and inflammatory responses due to hyperglycaemia may damage the retina or optic nerve [12,38,39].…”
Section: Resultsmentioning
confidence: 98%
“…This assumption has been supported by a study using a chick embryo model in which a high concentration of glucose injected on embryo development day (EDD) 1 resulted in 47.3% of embryonic eye malformations occurring on EDD 5 [37]. Second, enhanced oxidative stress and inflammatory responses due to hyperglycaemia may damage the retina or optic nerve [12,38,39].…”
Section: Resultsmentioning
confidence: 98%
“…Six conserved transcription factors (Pax-6-like, RXR, GLIS3, Elf-1-like, PNR, and ZBED1-like) are also downregulated in all four tissues in captive COTS. These may regulate the activation and repression of genes captive starfish across multiple tissues (German et al, 2013; Zhang et al, 2016; Jetten, 2018; Seifert et al, 2019). Oxidative stress appears to mediate the suppression of Pax6 gene in vertebrates (Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These may regulate the activation and repression of genes captive starfish across multiple tissues (German et al, 2013; Zhang et al, 2016; Jetten, 2018; Seifert et al, 2019). Oxidative stress appears to mediate the suppression of Pax6 gene in vertebrates (Zhang et al, 2016). Additionally, RXR receptor, GLIS3 and Elf-1 have all been shown to be involved in signalling in vertebrates, therefore potentially playing a role in the downregulation of cell-cell communication in captive COTS (German et al, 2013; Jetten, 2018; Seifert et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Orzáez et al showed that the administration of Apaf-1 inhibitor can reduce cytochrome-c release and apoptosome-mediated activation of procaspase 9 which in turn will prevent cell damage due to apoptosis [48]. Increased apoptosis in neonates born from mothers with gestational diabetes is known to be the cause for the malformation of brain, nervous system, heart, and eyes in neonates [47,49,50].…”
Section: Salacca Zalacca Peel Reduces Il-1β and Apoptosis Markers Expression Due To High Glucosementioning
confidence: 99%